2003
DOI: 10.1086/375323
|View full text |Cite
|
Sign up to set email alerts
|

New SX Phoenicis Stars in the Globular Cluster M53

Abstract: Through time-series CCD photometry of the metal-poor globular cluster M53 we have discovered eight new SX Phoenicis-type stars (labeled '' SXP1 '' to '' SXP8 ''). All the new SX Phoenicis stars are located in the blue straggler star region of the color-magnitude diagram of M53. One of these stars (SXP2) is found to have very closely separated pulsation frequencies: f 1 /f 2 = 0.9595, where f 1 and f 2 are the primary and secondary frequencies, respectively. This may be due to excitation of nonradial modes. Six… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 27 publications
(60 reference statements)
8
61
1
Order By: Relevance
“…We successfully identified SXP1, SXP2, SXP6, and SXP7 among these eight objects in our data (they are identical to our V73, V74, V75, and V76, respectively). From the data published by Jeon et al (2003), SXP4, SXP5, and SXP8 have too low amplitudes to be identified in our data. The situation is different for SXP3 which has a reasonably large amplitude of 0.1 mag according to Jeon et al (2003) but it is rather close to V66 and V67 and the limited resolution of our CCD chip did not enable us to separate their light variations.…”
Section: Short-period Variablescontrasting
confidence: 76%
See 3 more Smart Citations
“…We successfully identified SXP1, SXP2, SXP6, and SXP7 among these eight objects in our data (they are identical to our V73, V74, V75, and V76, respectively). From the data published by Jeon et al (2003), SXP4, SXP5, and SXP8 have too low amplitudes to be identified in our data. The situation is different for SXP3 which has a reasonably large amplitude of 0.1 mag according to Jeon et al (2003) but it is rather close to V66 and V67 and the limited resolution of our CCD chip did not enable us to separate their light variations.…”
Section: Short-period Variablescontrasting
confidence: 76%
“…With the aid of TFA, we considerably increased the reliability of detection of short-period, low-amplitude signals by filtering out low-frequency trends from the data whose amplitudes would have overwhelmed the intrinsic light variations of these objects. All of the short-period stars previously known in M53 were discovered by Jeon et al (2003) who used a 1.8-m telescope and PSF photometry. All of these objects are of SX Phe-type located in the blue straggler region of the color-magnitude diagram (CMD).…”
Section: Short-period Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…SX Phe stars are well known as distance indicators through their P-L relation (e.g. Jeon et al 2003). By adopting the P-L relation for the fundamental mode recently calculated by Cohen & Sarajedini (2012) for a sample of 77 double-mode SX Phe stars in Galactic globular clusters, which is of the form M V = −1.640(±0.110)−3.389(±0.090) log(P f ), we can calculate M V = 2.588 ± 0.157 mag for V6 assuming that it is pulsating in the fundamental mode.…”
Section: Sx Phoenicis Stars and Candidatesmentioning
confidence: 99%